Design, Synthesis and Pharmacological Screening of β-Amino-, Thiadiazole/Thiadiazine-Phosphonate Based Triazole Motifs as Antimicrobial/Cytotoxic Agents - Abdou Wafaa M.; Ganoub Neven A.; Sabry Eman (Acta Pharmaceutica)
Three different series of phosphonate derivatives, b-aminoand fused thiadiazolo/thiadiazine-phosphonates have been synthesized using the addition and/or addition-cyclization protocol of Horner-Wadsworth-Emmons (HWE) reagents to 1,2,4-triazole-3-thiols. The design of potentially antimicrobial and anticancer phosphor esters relied on the results of computer-assisted molecular modeling. All synthesized phosphonates were evaluated for their in vitro antimicrobial activities while anticancer properties were determined for eight out of twenty new phosphonates. The tested phosphonates, except for compounds that have a nitrile moiety, exhibited moderate to significant antimicrobial activity. Nevertheless, the most active compounds were fused thiadiazole-phosphonates, which inhibited the growth of both Gram-negative and Gram-positive bacteria better than b-aminophosphonates and fused thiadiazolophosphonates. In parallel, the antitumor activity screenings of selected phosphonates from each series and substrate 1 were also done. Their antitumor properties against ten carcinoma cell lines, including breast (MCF7, MDA-MB- 231/ ATCC, MDA-MB-435, BT-549), ovarian (IGROVI, OVCAR-3, SK-OV-3), prostate (PX-3, PU-145), and liver (HEPG2), were investigated. The results showed that all synthesized compounds reflected remarkable antitumor activity against breast (especially MDA-MB-231/ATCC and BT-549), and prostate carcinoma cell lines (PC-3 and DU-145), whereas a moderate to good effect on ovarian and liver cancer cells was observed.